Experimental investigation and FE modelling of the flexural performance of square and rectangular SRCFST members. (October 2020) - Wang, Wen-Da; Xian, Wei; Hou, Chao; Shi, Yan-Li
Abstract: In this study, experimental investigation and finite element (FE) modelling of the flexural performance of square and rectangular steel-reinforced concrete-filled steel tubular (SRCFST) members are carried out. Six square SRCFST specimens and four rectangular ones are fabricated and tested to obtain their failure modes, the strain data, the deformation and the moment capacity under four-point bending. The effects of profiled steel configuration, loading planes, shear-span ratios ( a / D ) and depth-to-width ratios ( D / B ) on the flexural performance of SRCFST members are evaluated. Moreover, the experimental data reported in this study are employed to verify the numerical model comprehensively. Thereafter, the verified FEA model is utilized to evaluate the stress distribution, the interaction between steel and concrete, the moment resisted by each component and the role of embedded profiled steel. Finally, the measured bending moment capacities are adopted to calibrate the accuracy of existing design method on SRCFST members stipulated in Eurocode 4 (EC4) (2004), while the results demonstrate that high accuracy for the prediction of bending moment capacity can be obtained.